2014
DOI: 10.5812/ircmj.20219
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin and Prevention of Hypotension during Hemodialysis

Abstract: Context:The occurrence of intradialytic hypotension (IDH) during hemodialysis (HD) continues to be a main problem in patients with ESRD (end-stage kidney disease). It also negatively affects health-related quality of life. We aimed to determine vasopressin effect in decreasing IDH.Evidence Acquisition:We reviewed clinical and experimental literature in a variety of sources, including PubMed, Current Content, Scopus, Embase, and Iranmedex regarding the possible effect of vasopressin administration in prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Nonmedication strategies for treating intradialytic hypotension, such as cardiovascular status optimization, UF rate minimization, and target-weight reassessment, should be prioritized. Medication options include midodrine, 71 arginine-vasopressin, [72][73][74][75][76] sertraline, 77,78 droxidopa, amezinium metilsulfate, 79 fludrocortisone, and carnitine. 71 In general, the evidence base for these strategies is relatively weak, with most studies being small and of short duration.…”
Section: Intradialytic Hypertension Nonementioning
confidence: 99%
“…Nonmedication strategies for treating intradialytic hypotension, such as cardiovascular status optimization, UF rate minimization, and target-weight reassessment, should be prioritized. Medication options include midodrine, 71 arginine-vasopressin, [72][73][74][75][76] sertraline, 77,78 droxidopa, amezinium metilsulfate, 79 fludrocortisone, and carnitine. 71 In general, the evidence base for these strategies is relatively weak, with most studies being small and of short duration.…”
Section: Intradialytic Hypertension Nonementioning
confidence: 99%
“…However, the hypertonic saline did increase serum osmolality, leading to increased endogenous AVP secretion and an increase in BP; a similar increase in BP was observed with direct exogenous AVP infusion in that study as well . Two other studies examined the administration of exogenous intranasal AVP analogs vs placebo administered just prior to the dialysis procedure in patients prone to IDH . Both studies showed that patients in the AVP group had fewer episodes of IDH and higher nadir BP compared with placebo.…”
Section: Effects Of Vasoconstrictor Medications On Idhmentioning
confidence: 52%
“…Toxoplasmosis is an opportunistic pathogen among immunocompromised patients including solid organ transplant recipients and it has been recognized as a potential donor-to-host transmission infection after transplantation (2-5). It can contribute in increment of morbidity and mortality in these patients (6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Dear Editormentioning
confidence: 99%